The second wave of the COVID-19 epidemic in Cuba: the sixth- and seventh-month flare-ups - Enrique Beldarraín-Chaple; Ileana R. Alfonso-Sánchez; María Vidal-Ledo (Social Medicine Publication Group, 2021)
In Cuba, the first cases of COVID-19 were diagnosed on March 11, 2020, that month 212 positives were accumulated (rate 2.9 x 100,000 inhabitants), they rose to 1,325 in April (11.8 x 100,000 inhabitants), on April 24 the largest number of cases of the epidemic was reported. In May, the accumulated cases were 2083 (rate 4.9 x 100,000), they decreased in June (265, rate 2.4 x 100,000), remaining endemic for several weeks. In August and September the number of positives increased in several provinces, while other provinces went up to 100 days without reporting cases. Severe and critically ill cases increased (32 severe in June and 317 in September and 12 critical in June and 73 in September). The increase in positives in those months was related to violations of health protocols to control transmission. In August, measures were established to regulate population mobility in the capital and in four other western provinces, and cases decreased at the end of September, although they remained high in the provinces of Havana, Ciego de Ávila and Matanzas (rates of 37 , 0; 113.0 and 13.3 x 100,000 inhabitants respectively). The decrease in cases showed the relevance of the measures, which were made more flexible at the end of September due to economic needs and to reactivate social life.The objective of this work is to describe the epidemiological situation of the months of August and September 2020 during the COVID-19 epidemic in Cuba.